Empowering the Thai Diaspora : Increasing Financial Literacy and Environmental Awareness in Accordance with the Principles of Green Economy on Muhammadiyah's Da'wah - Suranto, Suranto; Sari, Dhany Efita; Aisyah, Siti; Siregar, Yani Sukriyah; Jelita, Hanifah Intan Tria; Laksmi, Azarin Carissa Putri (Abdi Psikonomi, 2025)
The purpose of this community service is to improve financial literacy and environmental awareness of the Indonesian diaspora in Thailand. Situation analysis revealed a low level of knowledge in financial management and green economy practices within the community. The implementation method consisted of visual module-based training, the use of assistive technology (Google Lens), and a dakwah approach rooted in Islamic values. The activity was carried out at Lukmanulhakeem School, Yala, Southern Thailand, involving 24 participants, comprising teachers and students of the school. Pretest and posttest results indicated an increase in the average score from 4.50 to 4.95. More than 83.3% of participants were able to develop personal financial plans, while 87.5% expressed readiness to adopt environmentally compliant financial products. Furthermore, interactive discussions reflected the participants' enthusiasm for adopting green economy principles in daily life. Language barriers were addressed through the use of Google Lens as a translation aid, enabling participants to better understand foreign terms, module content, and measurement instruments for improved comprehension and skills development. These results demonstrate that the Muhammadiyah dakwah-based approach integrating green economy principles effectively enhanced the financial literacy and ecological awareness of the diaspora, while also building a foundation for the economic and social sustainability of the diaspora community in Thailand